Digital Economy as a Tool for Sustainable Development - M. V. Miroslavskaya (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2021)
The article shows the modern application of the digital economy in Russia, state participation in the development of the digital economy; a method for solving new problems and risks is proposed as a tool for ensuring sustainable development.The possibilities of using the digital economy for the SME sector have been identified. Further development prospects were considered, the main threats to the development of the SME sector were identified in the context of the implementation of the digital economy program.